2021
DOI: 10.54203/scil.2021.wvj53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Larvicidal Extract N-Hexane Lime Leaves (Citrus hystrix) on Larva Instar III Mosquito (Culex quinquefasciatus)

Abstract: Culex quinquefasciatus mosquitoes are a vector of transmission of several types of diseases, such as filariasis, Japanese encephalitis, and dirofilariasis. Larval control is the key strategy of disease control programs caused by vectors around the world because it can prevent larvae to enter the adult stage. Control of mosquito larvae that are often used is chemically controlled. Citrus hystrix is a natural plant and contains chemical compounds that have biological activity, such as flavonoids, carotenoids, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to the obtained results, 53.3% of infected women who lived in rural areas were in contact with cats, confirming that the main origin of infection could be having contact with cats either directly or through eating vegetables contaminated with the oocyst. Contacting livestock in rural areas and eating different types of meat could also be other risk factors as people are used to eating roast meat (locally called Kebab) which is usually undercooked (12,13).…”
Section: Qpcr Assay To Confirm Results Of Npcrmentioning
confidence: 99%
“…According to the obtained results, 53.3% of infected women who lived in rural areas were in contact with cats, confirming that the main origin of infection could be having contact with cats either directly or through eating vegetables contaminated with the oocyst. Contacting livestock in rural areas and eating different types of meat could also be other risk factors as people are used to eating roast meat (locally called Kebab) which is usually undercooked (12,13).…”
Section: Qpcr Assay To Confirm Results Of Npcrmentioning
confidence: 99%
“…quinquefasciatus larvae in vitro at 93.33% after 4 hours of observation. 39 Nano emulsion of essential oil of C. hystrix showed larvicidal and pupicidal activity on larva and pupa of Ae. aegypti and it is more environmentally friendly than temephos.…”
Section: Discussionmentioning
confidence: 96%
“…quinquefasciatus larvae based on morphology and biochemistry, such as total glucose, triacylglyceride (TAG), protein, and AChE levels, indicated that the essential oil can significantly decreased AChE levels after exposure for 24 h. 28 Alkaloid can degrade the cell membrane of the digestive tract, and interfere with the nervous system of larvae by inhibiting AChE activities. 39 The mutations in the ace-1 gene in survived larvae may play a role in the detoxification of the poison content in the extract leading to the survival of larvae. The ace-1 mutation in the Anopheles gambiae mosquito population from Cameroon is associated with most mosquitoes being alive after carbamate exposure.…”
Section: Discussionmentioning
confidence: 99%